PERBEDAAN MORALITAS SISWA ANTARA YANG BERSTATUS SANTRI DAN NON SANTRI DI MTS PERGURUAN MU’ALLIMAT CUKIR DIWEK JOMBANG - Qurotul Nguyun (JURNAL PENDIDIKAN ISLAM AL-ILMI, 2019)
Research on the differences Between Students Morality that is a Rasta and Non Rasta Mu'allimat Cukir College Diwek Mts Jombang. The purpose of  research is to know the morality of students are santri, to know the morality of non-status santri, and students to do know the difference between students of morality that is a Rasta and non Rasta in Mts College Mu'allimat cukir diwek stubs.This research uses a quantitative approach with design research Ekspost Facto with the kind of research field comparisons/Man Whitne, study researchers use research instrument in the creation of research instrument must be passing the test validity and  reliability in advance so that the instrument can be trusted their validity. By using purposive sampling, taking of the sample into account the techniques students are santri and non santri of students, 50 students comprising students are santri and students who are non santri.After the analysis, it was shown that the Sig value, 0.199> 0.05, which means H0 was accepted and HA was rejected, which means there was no difference in student morality between students with non-santri status in MTs of the Mualimat Cukir Diwek  in Jombang. Keywords: morality of students, students, non-santri